Preface - Soniewicka, Marta; Warmbier, Adriana (ETHICS IN PROGRESS, 2015)
The hereby introduction gives an insight into the topics and themes discussed in the hereby presented issue of the journal Ethics in Progress, devoted to the topic of transhumanism in its numerous contexts.